Macroeconomic Performance and Collective Bargaining: An International Perspective - Flanagan, Robert J (Journal of Economic Literature, 1999)
This paper critically reviews the research on how collective bargaining systems influence macroeconomic performance in industrialized countries. The review considers effects of bargaining level, coordination, and corporatist institutional arrangements. Key empirical results turn out to be quite fragile, and much of the paper explores issues of measurement and specification that account for the fragility. The paper concludes that complementarities between key institutions and between institutions and the economic environment may be more important for macroeconomic performance than the effects of individual institutions, and it suggests research strategies.